Reduction as way to reveal the thesis of natural attitude - Łaciak, Piotr (Folia Philosophica, 2010)
The paper presents Husserl’s conception of the transcendental reduction taken as a mode of revealing those constitutive achievements of consciousness which were covered in the natural attitude. This aspect of Husserl’s writings was pointed out by Ludwig Landgrebe, Paul Janssen and Shigeru Taguchi. Taking their works into account, the author focuses on reduction in terms of excluding the thesis of natural attitude. To exclude this thesis it is first of all necessary to reveal it and recognize as a thesis, for in natural attitude it is fulfilled anonymously and remains covered. Reduction of the thesis of natural attitude leads to its reflective revealing, that is refraining from its anonymous, mindless fulfilment. It is through revealing the thesis, taken as an experience of consciousness, that we recognize that the reality needs to be understood as a correlate of the thesis, and ultimately: correlate of subjectivity which works as fulfilling the thesis. Hence, anonymously fulfilled in natural attitude, the thesis on the world’s existence is recognized, thanks to the reduction, as a constitutive achievement of consciousness.